Tazkiyat Al-Nafs as Resilience Strategy to Deal with the Post-Pandemic Recession among Micro, Small, and Medium Enterprises (MSMEs) Actors - Atika Ulfia Adlina; Zaizul Abd Rahman; Muhammad Sakdullah; Dewi Aisyah; Ferizka Rizky Al Amin (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
This paper examines how resilience religiosity using the tazkiyat al-nafs technique is carried out by economic actors from the elements of Micro, Small, and Medium Enterprises (MSMEs) facing a post-pandemic recession. In-depth interviews were conducted with 27 MSME actors. The findings reveal that the pattern of tazkiyat al-nafs as a religiosity resilience used by economic actors from elements of Micro, Small, and Medium Enterprises (MSMEs) in facing the post-pandemic recession has succeeded in making it easier for them to adapt and create innovation and creativity to overcome post-pandemic recession conditions. On the other hand, MSME actors who are not in the tazkiyat al-nafs pattern have difficulty adjusting themselves in times of crisis.Contribution: The contribution of this paper is to provide a new understanding that maqāmāt can be used as a self-management technique when facing difficult times. In addition, maqāmāt can also be applied by ordinary people from Sufism teachings. Maqāmāt is a new way of religious resilience.